In vitro production and assessment of salt tolerant lines of Malaysian Indica Rice (Oryza sativa L.) cv. MARDI Siraj 297 - Sidek, Noorhazira (2022)
As most of other economically important crops, rice (Oryza sativa L.) is sensitive to salinity. Due to emerging salinity impacts on global food security, different strategies have been implemented including the development of salt tolerant varieties to minimize yield loss. Therefore, this study was conducted to produce salt tolerant lines of an importantly grown local rice cultivar, MARDI Siraj 297 through in vitro callus selection. The first objective of this study was to optimize the embryogenic callus induction medium. Sterilized MARDI Siraj 297 seeds were inoculated on MS basal medium supplemented with 0 to 3.5 mg/L 2,4- dichlorophenoxyacetic acid (2,4-D) and 0 to 0.5 mg/L kinetin (Kin) for 35 days. The MS medium supplemented with 2.0 mg/L 2,4-D and 0.2 mg/L Kin exhibited the maximum response in all callus growth parameters evaluated. Hence this combination was selected as the optimum medium for embryogenic calli proliferation in the subsequent experiments. The second objective was to produce, screen and select the salt tolerant calli. Embryogenic calli were treated in selection medium containing 0 to 150 mM NaCl for 5 months, followed by screening and selection of salt tolerant variants using morphology and biochemical markers. Normal callus morphology was observed in NaCl concentration up to 75 mM. The biochemical profile of these surviving calli showed that the salt tolerant lines had significantly higher content of proline, total soluble sugar, catalase activity, ascorbate peroxidase activity and K+/Na+ ratio compared to the non-tolerant control. Meanwhile, reduction of protein content and elevated MDA production was observed in these salt tolerant calli with increasing salinity level. The third objective involves the salt tolerance enhancement of the selected calli by supplementation of salicylic acid (SA) as phytoprotectant in the growth medium. The addition of 1.0 mM SA reduced the morphological injury while maximized the regeneration frequency and number of shoots as compared to the non-SA-treated calli. In the fourth objective, the regenerated salt tolerant plants (R0) were acclimatized. The evaluation of growth and agronomic traits found that 6 tolerant lines derived from 25 and 75 mM NaCl were morphologically normal and able to produce seeds of the first generation of salt tolerant lines (R1) while 2 lines derived from 100 mM NaCl were sterile. In the final objective, the comparison of agronomic traits between the R1 salt tolerant lines and control plant showed that the salt tolerant lines exhibited significantly improved agronomic traits, lower stress susceptibility index (SSI) and higher stress tolerance index (STI) in different salinity level during germination, vegetative and reproductive stage. In summary, in vitro selective salinity pressure in this study has successfully produced the R0, R1 and R2 generation of MARDI Siraj 297 salt tolerant lines. These established salt tolerant lines have potential to be utilized by farmers in salinity affected rice field areas. This study also provides a reliable protocol for the establishment of salt tolerant rice lines through tissue culture selection.